Quantitative Trait Loci Influencing Abdominal Fat Deposition and Functional Variability of the HPA Axis in the Rat - Marissal-Arvy, N.; Heliès, J.-M.; Tridon, C.; Moisan, M.-P.; Mormède, P. (Hormone and Metabolic Research, 2014)
With the aim to reveal common genomic regions influencing phenotypes related to HPA axis function and metabolism, we did a quantitative trait loci (QTL) study in a F2 population obtained from the cross-breeding between 2 contrasted rat strains, LOU/C and Fischer 344. QTL determining phenotypes related first to corticotropic function were searched: plasma corticosterone (Cort) in control and stress conditions, after a dexamethasone suppression treatment (glucocorticoid receptor related-effect), and mineralocorticoid receptor-mediated urinary response to aldosterone. Then, phenotypes related to metabolism were studied on the same animals: body composition, basal and post-insulin plasma glucose, plasma free fatty acids, leptin, and insulin. Finally, we analyzed the overlapping regions between these QTL and looked for candidate genes within these regions. The gene NR3C1 encoding the glucocorticoid receptor was confirmed to be central in the link between hypothalamic-pituitary-adrenal (HPA) axis function and fat deposition, and its metabolic consequences. Among the other candidate genes detected, most contain a glucocorticoid responsive element, strengthening our hypothesis of common genetic determinism between HPA axis and metabolism.
Keywords: QTL; metabolism; glucocorticoid; rat